Effect of different irrigation regimes on the quality attributes of monovarietal virgin olive oil from cv. “Cobrançosa” - A. A. Fernandes-Silva; J. B. Gouveia; P. Vasconcelos; T. C. Ferreira; F. J. Villalobos (Grasas y Aceites, 2013)
The aim of this study was to assess the effect of different irrigation strategies in virgin olive oil (VOO) composition and quality of cv. Cobrançosa, integrated in a protected denomination of origin of “Azeite de Trás-os-Montes” in the Northeast of Portugal. Three irrigation treatments were applied: T2-full irrigation that received a seasonal water equivalent to 100% of estimated crop evapotranspiration (ETc), T1-continuous deficit irrigation (30% ETc) and T0- rainfed treatment. Data were collected from two consecutive crop years (2005-2006). Irrigation regimes had a minor effect on standard quality indices (free fatty acids, peroxide value, K232 and K270) of VOO and in fatty acid composition. Total polyphenols decreased up to treatment T2, and were strongly related to the water stress integral, suggesting that the effect of irrigation on this variable occurs along the crop season and not just during the oil accumulation phase. A strategy of continuous deficit irrigation with only 30% of maximum ETc may have an advantageous effect, as it increased oil yield to more than double that of rainfed conditions while VOO quality was similar.